Wiley Encyclopedia of Composites 2011
DOI: 10.1002/9781118097298.weoc108
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Electrically Conducting Nano Composites Comprising Carbon Nanotubes/Intrinsically Conducting Polymer Systems

Abstract: Carbon nanotubes (CNTs) have drawn much attention in recent years. CNTs have remarkable properties, such as mechanical properties and electrical and thermal conductivity, thus offering opportunities for the development of new nanocomposites. A major problem in the dispersion of CNTs in a polymer is due to their tendency to agglomerate, thus interrupting the fine dispersion of CNTs in a matrix and partially losing the unique nanoscale effect. Intrinsically conducting polymers (ICPs) have drawn much attention si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 99 publications
0
6
0
Order By: Relevance
“…17 Polyaniline is one of the most extensively studied conducting polymers because of its simple preparation, high conductivity, and environmental stability. 17,18 PANI has the advantage of its numerous methods of production and the fact that it can be synthesized in the organic or aqueous phase, using agitation or sonication methods, as well as static interfacial, emulsion, or inverse emulsion polymerization. This work further describes and extends an ultrarapid inverse emulsion sonication technique reported elsewhere by the author.…”
Section: Introductionmentioning
confidence: 99%
“…17 Polyaniline is one of the most extensively studied conducting polymers because of its simple preparation, high conductivity, and environmental stability. 17,18 PANI has the advantage of its numerous methods of production and the fact that it can be synthesized in the organic or aqueous phase, using agitation or sonication methods, as well as static interfacial, emulsion, or inverse emulsion polymerization. This work further describes and extends an ultrarapid inverse emulsion sonication technique reported elsewhere by the author.…”
Section: Introductionmentioning
confidence: 99%
“…218 The first method employed to produce hybrid fibres from a combination of conducting polymers and CNTs was wet spinning. Mottaghitalab et al reported the wet spinning of PAni-CNT composite fibres, which exhibited excellent mechanical and electrical properties and were used as electrochemical actuators.…”
Section: Conducting Polymer-carbon Nanotube Fibresmentioning
confidence: 99%
“…Recently, a new class of materials made up of a combination of inorganic nanoparticles with organic polymeric compounds was introduced. CNTs and graphene are widely used as nanomaterials for sensors [ 39 ], and their association with PANI imparts synergetic properties to nanocomposit6es [ 40 , 41 , 42 , 43 ]. The outstanding structure and properties of CNTs (high stiffness, extraordinary flexibility, and tensile strength, along with high thermal and electrical conductivity) mean they can be used in a multitude of technological applications.…”
Section: Introductionmentioning
confidence: 99%